Let’s Learn Math: Design and Development of an Android-based Mathematics Learning Application for Dyscalculia Kids - Kee, Hui Jing; Ismail, Mohd Norasri (Applied Information Technology And Computer Science, 2023)
Mathematics is one of the core subjects that students should achieve. Nowadays, most jobs need to predominate mathematics skills. However, people who suffer from dyscalculia may have difficulty in crunching numbers. The existing applications to learn mathematics available on Google Play are yet to be implemented for the person with dyscalculia symptoms. Therefore, this project is proposed to design and develop a mobile mathematics learning application on the Android-based platform with a gamification approach based on the KSPK Pendidikan Khas syllabus and the functional and usability testing will be performed to the target users. The users targeted are children aged 4 to 6 years old. The Multimedia Mobile Content Development (MMCD) methodology is used to develop Let’s Learn Math application. Based on the System Usability Scale (SUS), the acceptable range was obtained with a resulting score of 91.88. This application is expected to assist dyscalculia people to learn basic numbers.